Better Students Ask More Questions.
1 Answer | add yours
We can write cos (-x) = cos (0-x), such as the following identity may now be used:
cos (a-b) = cos a*cos b + sin a*sin b
Let a = 0 and b = x
cos (0-x) = cos 0*cos x + sin 0*sin x
But cos 0 = 1 and sin 0 = 0.
cos (0 - x) = 1*cos x + 0*sin x
cos (0 - x) = cos x
Therefore, the identity cos(-x) = cos x is verified.
Posted by giorgiana1976 on August 18, 2011 at 12:45 AM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.